Kepler’s laws: inferring the mass of Sagittarius A* - Ferreira, Mateus Barbosa; Mesquita Oliveira, Adriano (Cadernos de Astronomia, 2026)
This article aims to present an investigative approach to the study of black holes in light of Newtonian Mechanics, with a mathematical formulation developed by a high school student. The proposal involves the use of fundamental concepts such as Newton’s Laws, Kepler’s Laws, and the Law of Universal Gravitation. The study begins with a historical and theoretical contextualization, followed by a brief discussion of the scientific confirmation of the existence of black holes, highlighting the case of Sagittarius A*, a supermassive object located at the center of the Milky Way. Through orbital analysis of stars near this object, based on literature data, and using Kepler’s Third Law, its mass was estimated. The data were processed using a spreadsheet, allowing for statistical analysis. The comparison between the obtained results, namely (4.46 ± 0.01) × 10⁶ M⊙, and those found in the literature showed an uncertainty of ≈ 4%. Thus, the potential of classical mechanics as an introductory tool in teaching advanced concepts in astronomy becomes evident.